New and efficient magnetic nanocomposite extraction using multifunctional deep eutectic solvent based on ferrofluid and vortex assisted-liquid–liquid microextraction: Determining primary aromatic amines (PAAs) in tetra-packed fruit juices. (30th August 2022) - Faraji, Mohammad; Ghanati, Kiandokht; Kamankesh, Marzieh; Aryanasab, Fezzeh; Mohammadi, Abdorreza
Graphical abstract: Highlights: A novel zirconium phosphate modified magnetic graphene oxide nanocomposite was prepared. A novel multifunctional ferrofluid was prepared by mixing the nanocomposite and deep eutectic solvent. The ferrofluid was employed for the determination of PAAs in tetra-packed fruit juices. The ferrofluid presents different and efficient interactions with PAAs. Phase separation was done by an external strong magnetic field without centrifugation. The level of PAAs in the tested juice sample was lower than permitted level (10 µg kg −1 ). Abstract: In this work, a novel magnetic nanocomposite solvent (MNCS) based on ferrofluid and multifunctional deep eutectic solvent (MDES) was synthesized and applied in vortex assisted-liquid–liquid microextraction (VA-LLME). The ferrofluid has been composed from zirconium phosphate (modified magnetic graphene oxide) and tetrabutylammonium bromide-octanoic acid deep eutectic solvent (MGO/α-ZrP@TBAB-OA). This efficient method was employed to determine primary aromatic amines including aniline, 4-methoxyanniline, 4, 4′-diaminodiphenylmethane, orthotoluidine, 2, 6-dimethylaniline, 2-naphtylamine in tetra-packed juice samples. The proposed method showed the excellent extraction efficiency of PAAs according to strong interactions of new extraction solvent including electrostatic, π-π, and hydrogen bonding attractions. The found levels of PAAs are lower than the limit of quantifications (2.0 µg L −1 ). Therefore, the migration of PAAs from packaging to the juice samples is lower than permitted level (<10 µg kg −1 ). The results indicated high potential use of the offered method to analyze aromatic amine compounds in foodstuff and biologic samples in the future.